Electron–positron pair creation from the vacuum by the Feshbach resonance. (14th March 2023) - Zhou, X X; Li, C K; Cao, X N; Fu, M; Lin, N S; Li, Y J
Abstract: Electron–positron pair (EPP) creation under Gaussian and super-Gaussian potential wells is studied using the computational quantum field theory. We find that the EPP creation rate decreases, while the positron spectra have better monochromaticity when the potential well is wider and gentler. The phenomenon is explained by the Feshbach resonance using the complex scaling method. The width of the Feshbach resonance is narrower in the wider and gentler potential well, and the narrower Feshbach resonance can lead to a lower creation rate and better energy monochromaticity. This study indicates that the width of the Feshbach resonance plays an important role in the EPP creation, and the Gaussian-type potential well has an advantage in tuning the Feshbach resonance width.